MiR-4664-3p as a potential diagnostic, prognostic, and immunotherapeutic biomarker in NSCLC: modulation of tumor progression through CD8 + T cell regulation - Yi, Chun; Zhang, Hao; Guo, Qianqian; Lu, Linzhu; Gao, Cong; Zhao, Yunlong; Su, Yan; Lu, Jing (Frontiers in Oncology, 2025)
IntroductionNon-small cell lung cancer (NSCLC) is one of the leading causes of cancer-related deaths worldwide, largely due to complex interactions within the tumor-immune microenvironment that limit treatment efficacy. MicroRNAs (miRNAs) play critical roles in the regulation of tumor progression and immune evasion. This study systematically evaluated the expression characteristics, clinical significance, and role of miR-4664-3p in tumor immune regulation in NSCLC.MethodsWe analyzed an NSCLC dataset from The Cancer Genome Atlas (TCGA) and identified miR-4664-3p as a potential diagnostic, prognostic, and immunotherapeutic biomarker. Bioinformatic approaches have been used to assess miRNA expression and clinical significance. The regulatory role of the miR-4664-3p/Protein Kinase C Beta (PRKCB) axis was further examined using correlation analysis, nomogram construction, and experimental validation in cell lines and animal models.ResultsMiR-4664-3p was significantly upregulated in NSCLC tissues and served as an independent predictor of poor prognosis. Its increased expression was linked to reduced immune cell infiltration and enhanced immune escape. PRKCB was validated as a direct downstream target of miR-4664-3p and showed a positive association with CD8 + T cell infiltration and favorable outcomes. Functional assays confirmed that miR-4664-3p promoted NSCLC cell proliferation, migration, and invasion. Conversely, the inhibition of miR-4664-3p increased PRKCB expression, boosted CD8 + T cell activity, strengthened anti-tumor immunity, and suppressed tumor growth.ConclusionThese results suggest that the miR-4664-3p/PRKCB axis is crucial in NSCLC progression and immune modulation. Hence, MiR-4664-3p is a potential diagnostic and prognostic indicator, as well as therapeutic target in immunotherapy strategies for NSCLC.